THE RELATIONSHIP BETWEEN POLITICAL IDEOLOGY AND MEDIA ORGANIZATIONAL COMMUNICATION PATTERNS: A THEORETICAL ANALYSIS OF AUTHORITARIAN, LIBERTARIAN, AND SOCIAL RESPONSIBILITY PRESS SYSTEMS - Ilham Irawan; Afriansyah Hasibuan; Sayuti Andhira (OPINI: Journal of Communication and Social Science, 2025)
The press functions as an essential component of mass communication systems that shapes public opinion, disseminates information, and supports social and political life. Differences in political ideology and systems of government have resulted in diverse press systems across countries. The Authoritarian Theory, Libertarian Theory, Social Responsibility Theory, and Communist Theory provide a theoretical framework to explain the relationship between the press, the state, and society. Using a qualitative literature-based approach, this study analyzes the characteristics and practical implementation of each press theory. The findings indicate that each theory reflects distinct levels of media freedom, state control, and social responsibility, which influence how the press operates within a particular political context. Understanding these theories is important for evaluating the role of the press in supporting democratic values, political stability, and public accountability.